2018
DOI: 10.1021/acsbiomaterials.8b00759
|View full text |Cite
|
Sign up to set email alerts
|

Ag2[Fe(CN)5NO] Nanoparticles Exhibit Antibacterial Activity and Wound Healing Properties

Abstract: Therapeutic agents harboring both wound healing and antibacterial activities have much demand in biomedical applications. Development of such candidates with clinically approved materials adds more advantages toward these applications. Recently, silver metal complex nanomaterials have been playing a major role in medical uses especially for antibacterial activity and wound healing. In this report, we designed and synthesized silver nitroprusside complex nanoparticles (abbreviated as AgNNPs) using sodium nitrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 74 publications
4
64
0
Order By: Relevance
“…The presence of silver has effectively accelerated the cell proliferation via restricting the inflammatory cells and removing the barrier during the re-epithelization process. 84,85 Adding to it, the involvement of graphene has provided an enhanced mechanical strength and ideal structural stability to the Cs-GAP100 nanobiocomposite film and prevented its easy degradation. It is also reported that graphene, silver, and polycationic peptide possess a remarkable antibacterial property that would further help in preventing the microbial growth at the wound site.…”
Section: Antibacterial Studymentioning
confidence: 99%
“…The presence of silver has effectively accelerated the cell proliferation via restricting the inflammatory cells and removing the barrier during the re-epithelization process. 84,85 Adding to it, the involvement of graphene has provided an enhanced mechanical strength and ideal structural stability to the Cs-GAP100 nanobiocomposite film and prevented its easy degradation. It is also reported that graphene, silver, and polycationic peptide possess a remarkable antibacterial property that would further help in preventing the microbial growth at the wound site.…”
Section: Antibacterial Studymentioning
confidence: 99%
“…The currently available silver‐based treatment for burns and wounds including silver carboxymethyl cellulose, silver alginate, silver sulfadiazine, etc., possess problems of less stability and toxicity in their native forms . The antibacterial properties of NPs are size dependent since only the ultrafine NPs with diameters of 1–10 nm present a preferential interaction with the bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the application of sterile surgical techniques, bacterial contamination is considered as a main clinical complication of current synthetic vascular grafts, especially for small‐diameter vascular grafts (SDVGs, <6 mm) which can cause graft failure (Kabirian, Amoabediny, Haghighipour, Salehi‐Nik, & Zandieh‐Doulabi, ; Kabirian, Ditkowski, Zamanian, Heying, & Mozafari, ; Pashneh‐Tala et al, ; Radakovic et al, ; Rao et al, ). Bacteria start to colonize immediately after implantation especially during the critical first 6 hr which is also known as the “decisive period.” Since the management of this period is directly related to success or failure of implantation and the host's defenses are not able to completely combat the infection process during this period (Zilberman & Elsner, ), antimicrobial agents are used in the form of systemic or controlled release systems.…”
Section: Introductionmentioning
confidence: 99%